Free tissue transfer as a vascular source for the vessel‐depleted neck. Issue 11 (21st July 2016) - Tsao, Chung‐Kan; Loh, Charles Yuen Yung; Barrera, Joaquim Megias
ABSTRACT: Background: Reconstructing head and neck defects postoncologic resection can be challenging. This problem is further amplified when tackling the vessel‐depleted or hostile neck. Free flaps still provide the gold standard of reconstructing such defects. However, with increasing reconstructions, recipient vessel options rapidly diminish. This article provides a technique and strategy in managing such difficult cases using previous free flap pedicles. It also highlights the importance of flap selection in paving the way for future successful reconstructions. Methods: We present a fifth sequential free flap reconstruction postoncologic buccal resection and mention the key steps taken to ensure the safe and successful reuse of previous free flap pedicles. Results: Intraoperative and postoperative photographs are clearly presented with a particular focus on the management of the recipient pedicle. Conclusion: Adequate planning and strategic selection of free flaps with long pedicles can provide the necessary vascular sources needed for future successful free flap head and neck reconstructions. © 2016 Wiley Periodicals, Inc. Head Neck 38 : E2515–E2518, 2016